INVESTIGATION OF THE EFFECTS OF USING CHEMICALLY ENHANCED WATER DURING WATER ALTERNATING GAS INJECTION ON OIL RECOVERY - SAMAKOUSH, SAEED MAJIDAlE (2012)
The field incremental recovery of immiscible water alternating gas (WAG) process is about 5-l 0% original oil in place (OOIP). A low recovery of the WAG process is associated with water blocking, gravity segregation, unfavorable mobility control, and decreased gas injectivity. To minimize the aforementioned problems a new EOR technique, named as chemically enhanced water alternating gas (CW AG), which significantly improves the performance of the WAG process, is proposed. The CW AG process uses alkaline, surfactant, and polymer as a chemical slug which is injected during WAG process to reduce the interfacial tension (IFT) and improve the mobility ratio, simultaneously. Our objectives were to design an ASP slug which can produce a low IFT aqueous system and a good mobility control, to demonstrate the EOR potential of the CW AG process both experimentally and numerically, and to identify important parameters involved in CWAG process. By screening the available chemicals, the ASP slug was designed by IFT measurement and microemulsion phase behaviour and its stability was checked before core floodiLg test. The performance of the CW AG process was compared with conventional WAG and alkaline-surfactant-polymer (ASP) floodings. The core flood data were history matched by fitting parameters of the rock and fluid properties measured in the experiments. History matching of the core flood model helped to optimize the experiments and was useful to evaluate the criticality of the parameters in the CW AG process that influence sweep efficiency.